Adaptación de lentes de contacto en paciente femenino de 49 años con miopía magna. - Arcos Esquivel, Jessenia Fernanda (2022)
Magna myopia (also known as pathological myopia or degenerative myopia) is considered when it exceeds 6 diopters, there is an excessive elongation of the eyeball that gives rise to an abnormal elongation or stretching of all structures, including the retina that can be thinned, having high myopia does not only consist of having many diopters, high myopia are much more likely to develop eye complications such as glaucoma, cataracts or retinal detachment, this risk is greater the more elongated the eyeball is. Nowadays, any type of prescription and refractive problem can be corrected with contact lenses, even contact lenses are indicated in pathologies of the ocular surface that have caused an irregularity, such as in cases of corneal transplants or keratoconus, the great advantage for Compensation for high myopia is the elimination of aniseikonia, that is, the image difference that can occur between the two eyes or the decreased size produced by an ophthalmic lens in spectacles. All myopic people, when putting on our glasses, see the world much smaller than it really is, this entails a sensory adaptation that we suffer with the changes in prescription, but thanks to contact lenses, as they are directly forming a single optical system with the eye, this does not occur, which gives a sensation of improvement in optical quality and even in the field of vision as they are not limited by the frame of the glasses, which is why this case focuses on improving visual quality with the use of lenses of contact by having a superior correction to the frame lens and avoiding the distance to the vertex.